HLA-G Expressing Immune Cells in Immune Mediated Diseases - Contini, P.; Murdaca, Giuseppe; Puppo, Francesco; Negrini, Simone (Frontiers in Immunology, 2020)
HLA-G is a HLA class Ib antigen that possesses immunomodulatory properties. HLA-G-expressing CD4+ and CD8+ T lymphocytes, NK cells, monocytes, and dendritic cells with immunoregulatory functions are present in small percentages of patients with physiologic conditions. Quantitative and qualitative derangements of HLA-G+ immune cells have been detected in several conditions in which the immune system plays an important role, such as infectious, neoplastic, and autoimmune diseases as well as in complications from transplants and pregnancy. These observations strongly support the hypothesis that HLA-G+ immune cells may be implicated in the complex mechanisms underlying the pathogenesis of these disorders.